EXPLORING THE IMPACT OF PERSONAL REASONS AND PROGRAM EVALUATION ON INTERNATIONAL STUDENTS' HIGHER EDUCATION DESTINATION CHOICE IN MALAYSIA: A COMPARATIVE STUDY IN PUBLIC UNIVERSITY - Nur Azureen Abd Hadi; Prof. Madya Dr. Mazuri Binti Abd. Ghani (International Journal of Accounting, Finance and Business, 2023)
Traditionally, public universities were responsible for providing undergraduate and graduate studies. In turn, the higher education (HE) environment has become increasingly competitive and institutions have to compete for the recruitment of students in the market. Internationalization of higher education is becoming a common phenomenon in the world market nowadays. One of the reasons that lead to this competition is the contribution of international students to the economic activities in the host country. Thus, it is very important for marketers to know the factors that influence the study intention of prospective students and to understand the nature of the relationship among them. These factors are significant from the perspective of the Higher Education Institutions (HEI) marketing strategy planning for international student recruitment. The objective of this paper is to explore the impact of personal reason and Programme Evaluation towards international students’ motivation in choosing HEI in Malaysia as their destination. Three hundred international students in 20 public universities were participating in this study. Questionnaires were distributed which consist of four sections: Respondent Demographic Information, Higher Educational Destination Choice, Personal Reasons and Program Evaluation. Thus from this study it show that programme evaluation become the main reason as compare to the personal reason in choosing HEI in Malaysia.